A second species of Bittacus Latreille, 1805 (Mecoptera: Bittacidae) from Hainan Island, China - Chen, Jing; Hua, Baozhen (Zootaxa, 2011)
Bittacus diaoluoshanus sp. nov., the second species of Bittacidae (Mecoptera) from Hainan Island, China is described from Diaoluoshan National Forest Park. The new species is separated from other hangingflies of Bittacus by two crossveins below pterostigma; four tawny brown spots each at ORs, FRs, OM, and the distal end of CuP; one tawny stripe along apical margin from pterostigma to beyond apex; absence of Av; and male epandrial appendages subquadrangular at lateral aspect.